Policing the Boundaries: The “Mission Street Station Scene” in Philip K. Dick’s Do Androids Dream of Electric Sheep? (1968) - Panka, Dániel (Hungarian Journal of English and American Studies, 2021)
The essay focuses on the “Mission Street Station” episode in Philip K. Dick’s Do Androids Dream of Electric Sheep? (1968). The episode revolves around two central problems: the human/android divide and fake realities. The first part of the paper concentrates on theories of classification and analyses the problems of the Voigt-Kampff test understood as a classificatory apparatus. The second part focuses on the Mission Scene as a fake reality and identifies a potentially problematic race-focused reading. Dick, a prolific essayist and public speaker, expressed his preoccupation with questions that constitute the conceptual core of the scene on several occasions. Therefore, the essay also relies on the author’s nonfiction to discover and establish the importance of the oft-neglected Mission Scene in the novel’s critical reception. (DP)